Human Rights Regime: Between Universality and Cultural Relativism, An Indonesian Experience - Susetyo, Heru (Indonesian Journal of International Law, 2019)
Universal Declaration of Human Rights 1948 come with the idea that human rights are all universal. Vienna Declaration and Programme of Action 1993 strengthen the universalism of human rights by claiming that and interdependent and interrelated. The international community must treat human rights globally in a fair and equal manner, on the same footing, and with the same emphasis. While the significance of national and regional particularities and various historical, cultural and religious backgrounds must be borne in mind, it is the duty of States, regardless of their political, economic and cultural systems, to promote and protect all human rights and fundamental freedoms. And here is the problem. Indonesia is a member of the United Nations. Indonesia adopted UDHR 1948 and made it as the primary source of National Human Rights Provision (Law No. 39/ 1949). However, in practice, there are a lot of challenges in implementing universal human rights in Indonesia. Cultural relativism exists. This paper, therefore, will explore the complexity of Human Rights regime in Indonesia among various cultural relativism surrounding it by using legal and normative approach. The research found that international human rights law in Indonesia can not be implemented in the same manner as applied in the Western world. Instead, it needs to consider local and regional values, as well.